Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy

Using acid to improve credibility assessments with written and audio statements - Montalvo, L.; Hallinan, C.; Hiscock-Anisman, C.; Morrissey, D.; Bonilla, Y.; Colwell, K. (American Journal of Forensic Psychology, 2013)
Investigators are continually faced with the task of detecting deception. Assessment Criteria Indicative of Deception (ACID) is a system of interviewing and credibility assessment that maximizes verbal cues to detect deception, and teaches content analysis that highlights attempts to withhold, distort, or manipulate information. The ACID technique has been successful in discriminating honest from deceptive statements when credibility determinations are made either by statistical methods or trained raters. Unfortunately, the training has required several hours and application has required the time-consuming process of transcription. The current study demonstrates the utility of ACID following a brief training, and compares the credibility ratings made from analysis of transcripts to the credibility ratings made from the analysis of audio recordings. Twenty-nine university undergraduate and graduate students read or listened to a series of eight transcripts. Raters were provided with accounts before training and 4 accounts after training. Prior to training, raters performed at 55% accuracy. Following training, raters performed at 71% accuracy. Additionally, there was an untrained control group that performed at 53% accuracy. Of note, the post-training performance was identical for accounts presented in written and audio formats. In sum, the ACID technique was reliable, valid, easy to train, and showed that accurate decisions can be made from simple audio recordings. Copyright 2013 American Journal of Forensic Psychology,.
Keywords: accuracy; adult; article; assessment criteria indicative of deception; audiology; clinical assessment tool; clinical decision making; clinical education; content analysis; controlled study; deception; dept.psy; human; human experiment; meaningful use criteria; reliability; statistical analysis; validity; written language; ⛔ No DOI found

Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
17 citations (Crossref) [2023-10-31] Place: United States Stiver, Kelly A. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. stiverk1@southernct.edu
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior; Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models; Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior; Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon

Development of phonological constancy: 19-Month-Olds, but not 15-Month-Olds, identify words in a non-native regional accent - Mulak, Karen E.; Best, Catherine T.; Tyler, Michael D.; Kitamura, Christine; Irwin, Julia R. (Child Development, 2013)
By 12months, children grasp that a phonetic change to a word can change its identity (phonological distinctiveness). However, they must also grasp that some phonetic changes do not (phonological constancy). To test development of phonological constancy, sixteen 15-month-olds and sixteen 19-month-olds completed an eye-tracking task that tracked their gaze to named versus unnamed images for familiar words spoken in their native (Australian) and an unfamiliar non-native (Jamaican) regional accent of English. Both groups looked longer at named than unnamed images for Australian pronunciations, but only 19-month-olds did so for Jamaican pronunciations, indicating that phonological constancy emerges by 19months. Vocabulary size predicted 15-month-olds' identifications for the Jamaican pronunciations, suggesting vocabulary growth is a viable predictor for phonological constancy development.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-753-306-501-490 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Acoustic Stimulation; Female; Fixation; Ocular; Humans; Infant; Language Development; Male; Perceptual Masking; Phonetics; Psychomotor Performance; Recognition (Psychology); Speech Perception; Vocabulary; article; auditory stimulation; dept.psy; eye fixation; female; human; infant; language development; linguistics; male; perception; phonetics; physiology; psychomotor performance; recognition; speech perception

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-953-404-245-599, lens.org/132-483-465-914-642 tex.type: [object Object]
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning; Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models; Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed

Assessment Criteria Indicative of Deception: An Example of the New Paradigm of Differential Recall Enhancement - Colwell, Kevin; Hiscock-Anisman, Cheryl; Fede, Jacquelyn (Applied Issues in Investigative Interviewing, Eyewitness Memory, and Credibility Assessment, 2013)
The present chapter details the historical and conceptual evolution of a new paradigm in statement analysis that has developed over the past 20 years. There has been an increasing awareness of the importance of interviewing designed to facilitate the detection of deception as a necessary component of statement analysis (Colwell, Hiscock, & Memon, 2002; Hartwig & Bond, 2011; Hernández-Fernaud & Alonso-Quecuty, 1997; Koehnken, Schimossek, Ascherman, & Hofer, 1995; Vrij, Fisher, Mann, & Leal, 2006). Subsequently, the work of multiple researchers has created a zeitgeist that has nurtured and informed the development of this new paradigm. This chapter begins by providing a quick overview of the various lines of research that comprise this paradigm. Attention is then given to credibility assessment and statement content criteria that discriminate honest from deceptive responding. Then, the focus is on strategies of impression management and the subjective experience of respondents during an investigative interview. This sets the stage for a discussion of investigative interviewing structure and techniques that facilitate the detection of deception through the process of differential recall enhancement (DRE: Colwell et al., 2012). Finally, this chapter considers in detail an approach to interviewing and assessment that is representative of the new paradigm.
Citation Key Alias: lens.org/131-463-202-689-32X
Keywords: Content Criterion; Free Recall; Impression Management; Present Volume; Target Event; dept.psy

Sharing of potential nest sites by Etheostoma olmstedi males suggests mutual tolerance in an alloparental species. - Stiver, Kelly A; Wolff, Stephen H; Alonzo, Suzanne H (PloS one, 2013)
When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and individuals could have each occupied a potential nest site without same-sex sharing. Males were more likely to share a nest site with one other when the difference in size between them was larger rather than smaller. There was no evidence that female sharing was dependent on their relative size. Fish were generally more likely to use and share larger sites, in accordance with the greater relative surface area they offered. We discuss how one or both sharing males may potentially benefit, and how male sharing of potential nest sites could relate to female mating preferences. Tessellated darter males are known to provide alloparental care for eggs but this occurs without any social contact between the alloparent and the genetic father of the young. Thus, the suggestion that they may also share sites and maintain social contact with reproductive competitors highlights the importance of increased focus on the potential complexity of reproductive systems.
6 citations (Crossref) [2023-10-31] Place: United States Stiver, Kelly A. Psychology Department, Southern Connecticut State University, New Haven, Connecticut, USA. stiverk1@southernct.edu
Keywords: *Behavior; Animal; *Nesting Behavior; *Perches/ph [Physiology]; *Reproduction; Animals; Behavior; Animal; Etheostoma olmstedi; Female; Male; Nesting Behavior; Perches; Reproduction; Sexual Behavior; Animal; animal behavior; article; competitor species; controlled study; dept.psy; female; fish; male; male animal; mate choice; nesting; nonhuman; peer-reviewed; population density; population size; sex difference; social behavior; symbiosis